«The Last Ally»: Russian-Belarusian Relations at the Present Stage - O. B. Nemensky (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The article is devoted to relations between Belarus and Russia today. A survey of the history of relations between the two countries over the past 10-15 years, the formation of the modern ideology of the Belarusian foreign policy. aspect of economic relations between the two countries and internal political discussions in Belarus ’s foreign policy in the East. Particular attention is paid to the project of the Union State of Russia and Belarus, the problems of the participation of the Republic of Belarus in integration projects with Russia.